Analysis of tanshinone IIA induced cellular apoptosis in leukemia cells by genome-wide expression profiling - Liu Chang; Li Jianqin; Wang Liangjie; Wu Fuqun; Huang Linfang; Xu Yue; Ye Jieyu; Xiao Bin; Meng Fanyi; Chen Shilin; Yang Mo (BMC, 2012)
Abstract Background Tanshinone IIA (Tan IIA) is a diterpene quinone extracted from the root of Salvia miltiorrhiza, a Chinese traditional herb. Although previous studies have reported the anti-tumor effects of Tan IIA on various human cancer cells, the underlying mechanisms are not clear. The current study was undertaken to investigate the molecular mechanisms of Tan IIA's apoptotic effects on leukemia cells in vitro. Methods The cytotoxicity of Tan IIA on different types of leukemia cell lines was evaluated by the 3-[4,5-dimethylthiazol-2,5]-diphenyl tetrazolium bromide (MTT) assay on cells treated without or with Tan IIA at different concentrations for different time periods. Cellular apoptosis progression with and without Tan IIA treatment was analyzed by Annexin V and Caspase 3 assays. Gene expression profiling was used to identify the genes regulated after Tan IIA treatment and those differentially expressed among the five cell lines. Confirmation of these expression regulations was carried out using real-time quantitative PCR and ELISA. The antagonizing effect of a PXR inhibitor L-SFN on Tan IIA treatment was tested using Colony Forming Unit Assay. Results Our results revealed that Tan IIA had different cytotoxic activities on five types of leukemia cells, with the highest toxicity on U-937 cells. Tan IIA inhibited the growth of U-937 cells in a time- and dose-dependent manner. Annexin V and Caspase-3 assays showed that Tan IIA induced apoptosis in U-937 cells. Using gene expression profiling, 366 genes were found to be significantly regulated after Tan IIA treatment and differentially expressed among the five cell lines. Among these genes, CCL2 was highly expressed in untreated U-937 cells and down-regulated significantly after Tan IIA treatment in a dose-dependent manner. RT-qPCR analyses validated the expression regulation of 80% of genes. Addition of L- sulforaphane (L-SFN), an inhibitor of Pregnane × receptor (PXR) significantly attenuated Tan IIA's effects using colony forming assays. Conclusions Tan IIA has significant growth inhibition effects on U-937 cells through the induction of apoptosis. And Tan IIA-induced apoptosis might result from the activation of PXR, which suppresses the activity of NF-κB and lead to the down-regulation of CCL2 expression.